Aortic relative pressure components derived from four‐dimensional flow cardiovascular magnetic resonance - Lamata, Pablo; Pitcher, Alex; Krittian, Sebastian; Nordsletten, David; Bissell, Malenka M.; Cassar, Thomas; Barker, Alex J.; Markl, Michael; Neubauer, Stefan; Smith, Nicolas P. (Magnetic resonance in medicine, 2014)
Purpose To describe the assessment of the spatiotemporal distribution of relative aortic pressure quantifying the magnitude of its three major components. Methods Nine healthy volunteers and three patients with aortic disease (bicuspid aortic valve, dissection, and Marfan syndrome) underwent 4D‐flow CMR. Spatiotemporal pressure maps were computed from the CMR flow fields solving the pressure Poisson equation. The individual components of pressure were separated into time‐varying inertial (“transient”), spatially varying inertial (“convective”), and viscous components. Results Relative aortic pressure is primarily caused by transient effects followed by the convective and small viscous contributions (64.5, 13.6, and 0.3 mmHg/m, respectively, in healthy subjects), although regional analysis revealed prevalent convective effects in specific contexts, e.g., Sinus of Valsalva and aortic arch at instants of peak velocity. Patients showed differences in peak transient values and duration, and localized abrupt convective changes explained by abnormalities in aortic geometry, including the presence of an aneurysm, a pseudo‐coarctation, the inlet of a dissection, or by complex flow patterns. Conclusion The evaluation of the three components of relative pressure enables the quantification of mechanistic information for understanding and stratifying aortic disease, with potential future implications for guiding therapy. Magn Reson Med 72:1162–1169, 2014. © 2013 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.